2009
DOI: 10.1111/j.1600-0404.1990.tb00986.x
|View full text |Cite
|
Sign up to set email alerts
|

Bromocriptine blood levels after the concomitant administration of levodopa, amantadine and biperiden in Parkinson's disease

Abstract: We recently demonstrated that when different drugs (mainly used for the treatment of Parkinson's disease) are administered in combination they interfere with the availability of bromocriptine in the brain of rats (striatum and hypothalamus). In the present study performed with parkinsonian patients, we measured plasma levels of bromocriptine (RIA) over 4h after giving orally 5 mg bromocriptine alone; together with levodopa 250 mg plus 25 mg DCI (10 patients); with 100 mg amantadine HC1 (5 patients) and with bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…17 A significant decrease of bromocriptine plasma levels, which may result from an interference of levodopa comedication with bromocriptine metabolism in the liver, has been reported. 18 Low (1.5 mg/d) and high (4.5 mg/d) pramipexole doses administered concomitantly with levodopa did not alter levodopa bioavailability in a double-blind, placebo-controlled trial. 19 There was no pharmacokinetic interaction reported under coadministration of ropinirole and levodopa in PD patients not previously treated with dopamine agonists.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…17 A significant decrease of bromocriptine plasma levels, which may result from an interference of levodopa comedication with bromocriptine metabolism in the liver, has been reported. 18 Low (1.5 mg/d) and high (4.5 mg/d) pramipexole doses administered concomitantly with levodopa did not alter levodopa bioavailability in a double-blind, placebo-controlled trial. 19 There was no pharmacokinetic interaction reported under coadministration of ropinirole and levodopa in PD patients not previously treated with dopamine agonists.…”
Section: Discussionmentioning
confidence: 91%
“…On the other hand, it has been shown that chronic bromocriptine therapy has no effects on levodopa pharmacokinetics in patients with Parkinson disease 17 . A significant decrease of bromocriptine plasma levels, which may result from an interference of levodopa comedication with bromocriptine metabolism in the liver, has been reported 18 …”
Section: Discussionmentioning
confidence: 99%